Arch Cube Esperienze di progettazione architettonica assistita - Gasperini, Massimo (Cataloghi e collezioni, 2006)
The volume collects the results of a course in "Assisted architectural design" which experimented with some innovative aspects in the teaching of Drawing. The new frontier is now represented by computer tools and very complex processing programs that incorporate all the previous techniques and propose new ones, becoming for the architect the main instrument of restorative and expressive potential. The experience involved the course students not only in learning the most up-to-date computer graphics programs, but above all in the development of this new expression technique in close relation to a design experience.